POLICY IMPERATIVES FOR CONTROL OF MARKET EXCHANGE FAILURE IN THE CASHEW NUT INDUSTRY IN TANZANIA - Adam Meshack Akyoo; Zena T. Mpenda (European Scientific Journal, ESJ, 2014)
This study examined the root causes of incessant market failure problem facing Tanzanian cashew nut industry. The overarching hypothesis was that the industry challenges are both structural and institutional. Competition status and economic coordination in the industry were thus duly scrutinized. Key informant and questionnaire interviews were carried out with key industry stakeholders and cashew farmers respectively. Data analysis entailed operationalizing the Institutional Analysis and Development framework, the DFID Competition Assessment Framework and estimating the Stochastic Frontier Production Model. Results showcased a systematic positive effect of the Warehouse Receipt System (WRS) on indicative and final producer prices over the years. Concentration ratio results professed the industry as being fairly concentrated and hence oligopolistic. Farmers’ input use efficiency was calculated at 51% on average suggesting that majority could be high cost producers. The WRS was vindicated as an effective system for the industry though its high transaction costs due to hiked administrative costs, weak institutional arrangements along the value chain, cooperative monopoly and inadequate enforcement of underlying regulations counteract its strength. Fair competition in the industry is stifled by clandestine buyer collusion and predatory pricing at the expense of local processing. Production cost would overstate indicative price if used as a basis for its setting given inefficient farmers. For better results the industry needs to depoliticize, change warehouses’ ergonomics, eliminate unnecessary WRS administrative costs, break cooperative monopoly to accommodate private buyers’ participation, strengthen regulatory enforcement mechanisms, restore export parity pricing procedures and establish an advisory to sieve conflicting scholar recommendations.